“I am the first of my kind to see it”: Observation and Authorship in Mina Hubbard’s Performance as Labrador Explorer, 1905-1908 - Crooks, Katherine (Acadiensis, 2023)
This article focuses on Canadian Mina Hubbard’s expedition through the Labrador-Ungava Peninsula in 1905. In so doing, it examines the notion of the northern non-Indigenous explorer/traveller as witness. It considers two practices that were essential to Hubbard in the construction and performance of her identity as an explorer: empirical observation and authorship. Hubbard’s efforts to present herself as a reliable northern witness, in contest with her wilderness guides, also highlight the kinds of racialized, classed, and gendered identities that were excluded from the work of northern exploration around the turn of the century.